Scale-up strategy for yeast single cell oil production for Rhodotorula mucilagenosa IIPL32 from corn cob derived pentosan. (August 2020) - Banerjee, Ayan; Sharma, Tripti; Nautiyal, Abhilek K.; Dasgupta, Diptarka; Hazra, Saugata; Bhaskar, Thallada; Ghosh, Debashish
Graphical abstract: Highlights: Methodology of scale-up procedure for yeast single cell oil (SCO) production. Rhodotorula mucilagenosa IIPL32 cultivated in corncob prehydrolysate in fed-batch mode. Importance of the rheological behaviour of fermentation broth. Abstract: This work was aimed to strategically scale-up the yeast lipid production process using Reynolds number as a standard rheological parameter from 50 mL to 50 L scale. Oleaginous yeast Rhodotorula mucilaginosa IIPL32 was cultivated in xylose rich corncob hydrolysate. The fermentation process for growth and maturation was operated in fed-batch with two different C/N ratios of 40 and 60. The hydrodynamic parameters were used to standardize and represent the effect of rheology on the fermentation process. The growth pattern of the yeast was found similar in both shake flask and fermenter with the maximum growth observed at 48 h. The lipid yield increased from 0.4 g/L and 0.5 g/L to 1.3 g/L and 1.83 g/L for 50 mL to 50 L for C/N ratio 40 and 60 respectively. The increase in productivity during the growth phase and lipid accumulation during the maturation phase showed that the scale-up strategy was successful.